The Degree of Application of Total Quality Management in the Executive Committee of the General Sports Federation in Lattakia - عصام صديق ماشي; وائل مارون معوض; رعد حسن الصرن (Latakia University Journal -Medical Sciences Series, 2022)
The aim of the research is to know the degree of application of total quality management in the Executive Committee of the General Sports Federation in Lattakia, according to the following areas: effective leadership, quality planning, guidance and evaluation, information and communication network. The research adopted the descriptive analytical method, and the research community consisted of all the members of the Executive Committee and the workers in the Executive Committee of the General Sports Federation in Lattakia, which numbered (125) members and workers, and the research sample was a simple random sample of (80) members and workers from the total community The research, at a rate of (64%), which is a representative percentage, where the questionnaire as a research tool was distributed to them to know the degree of application of total quality management in the Executive Committee of the General Sports Federation in Lattakia in the areas of: effective leadership, quality planning, guidance and evaluation, information and communication network. The results showed that the degree of application of total quality management in the Executive Committee of the General Sports Federation in Lattakia Governorate was low, and the effective leadership field came in the first place with a percentage (50.75%), followed by the field of quality planning (50%), followed by the field of information and communication network with a percentage (47.88%), followed in the last rank by the field of guidance and evaluation (40.25%).